Thoracic aorta 3D hemodynamics in pediatric and young adult patients with bicuspid aortic valve. Issue 4 (22nd January 2015) - Allen, Bradley D.; van Ooij, Pim; Barker, Alex J.; Carr, Maria; Gabbour, Maya; Schnell, Susanne; Jarvis, Kelly B.; Carr, James C.; Markl, Michael; Rigsby, Cynthia; Robinson, Joshua D.
<x xml:space="preserve">Abstract</x> Background To evaluate the 3D hemodynamics in the thoracic aorta of pediatric and young adult bicuspid aortic valve (BAV) patients. Methods 4D flow MRI was performed in 30 pediatric and young adult BAV patients (age: 13.9 ± 4.4 (range: [3.4, 20.7]) years old, M:F = 17:13) as part of this Institutional Review Board‐approved study. Nomogram‐based aortic root Z‐scores were calculated to assess aortic dilatation and degree of aortic stenosis (AS) severity was assessed on MRI. Data analysis included calculation of time‐averaged systolic 3D wall shear stress (WSSsys) along the entire aorta wall, and regional quantification of maximum and mean WSSsys and peak systolic velocity (velsys) in the ascending aorta (AAo), arch, and descending aorta (DAo). The 4D flow MRI AAo velsys was also compared with echocardiography peak velocity measurements. Results There was a positive correlation with both mean and max AAo WSSsys and peak AAo velsys (mean: r = 0.84, P < 0.001, max: r = 0.94, P < 0.001) and AS (mean: rS = 0.43, P = 0.02, max: rS = 0.70, P < 0.001). AAo peak velocity was significantly higher when measured with echo compared with 4D flow MRI (2.1 ± 0.98 m/s versus 1.27 ± 0.49 m/s, P < 0.001). Conclusion In pediatric and young adult patients with BAV, AS and peak ascending aorta velocity are associated with increased AAo WSS, while aortic dilation, age, and body surface area do not significantly impact AAo hemodynamics. Prospective studies are required to establish the role of WSS as a risk‐stratification tool in these patients. J. Magn. Reson. Imaging 2015;42:954–963.